Experimental Investigation for the Removal of Toxic Gases from Vehicle Exhaust using Non-Thermal Plasma (Journal of Engineering, 2018)
In this study, the use of non-thermal plasma theory to remove toxic gases emitted from a vehicle was experimentally investigated. A non-thermal plasma reactor was constructed in the form of a cylindrical tube made of Pyrex glass. Two stainless steel rods were placed inside the tube to generate electric discharge and plasma condition, by connecting with a high voltage power supply (up to 40 kV). The reactor was used to remove the contaminants of a 1.25-liter 4-cylinder engine at ambient conditions. Several tests have been carried out for a ranging speed from 750 to 4,500 rpm of the engine and varying voltages from 0 to 32 kV. The gases entering the reactor were examined by a gas analyzer and the gases concentration ratio are recorded in the inlet of the reactor and after they are released from the reactor after the chemical processes associated with the electric discharge applied to the gases inside the reactor. As a final result, convergent removal rates of gases were obtained but under different conditions, the best ratios were: NOx 72.32% (at a rotational speed of 3500 rpm and an applied voltage of 25kV, HC 69.46% (at 1500 rpm and 30kV, CO 66.66% (at 3000 rpm and a range of voltage from 25 to 32kV) and CO2 72.44% (at 3500 rpm and 27 kV).